DIVERSITY, DISTRIBUTION AND CONSERVATION OF RARE, ENDEMIC ORCHID SPECIES IN NAM NGUM UPSTREAM PROTECTION FOREST AREA OF XIENG KHOUANG PROVINCE, LAO PDR - Van Tu, Nguyen; Bounyavet, Latdavan (Journal of Forestry Science and Technology, 2019)
The Nam Ngum Upstream protection forest area (NUPA) is known as the repository of biodiversity. It supports 1,200 species of angiosperms. The orchidaceae is among the dominant family of angiospecies and a highly evolved family among the monocotyledon. The species of this family are facing tremendous pressure due to habitat degradation, overexploitation and changing environmental conditions. Therefore, while exploring the floristic diversity of NUPA, attempts were made to explore the orchid diversity, distribution patterns, nativity, endemism, threat categories, and local uses. Total 31 species of the orchids representing 10 genera were recorded between 250 - 1,500 m amsl. Of these, 31 species were native, 3 species endangered, and 2 species vulnerable. These species are represented in three forest types and are used for curing various diseases/ailments by the inhabitants of the buffer zone of NUPA. Due to habitat degradation, the populations of these species are decreasing fast. The overexploitation, habitat degradation and changing environmental conditions of these species has led to rapid population depletion. Therefore, appropriate strategy has been suggested for the conservation and management of these orchids.